Decision making preferences in the medical encounter - a factorial survey design - Keller Heidi; Krones Tanja; Müller-Engelmann Meike; Donner-Banzhoff Norbert (BMC, 2008)
Abstract Background Up to now it has not been systematically investigated in which kind of clinical situations a consultation style based on shared decision making (SDM) is preferred by patients and physicians. We suggest the factorial survey design to address this problem. This method, which so far has hardly been used in health service research, allows to vary relevant factors describing clinical situations as variables systematically in an experimental random design and to investigate their importance in large samples. Methods/Design To identify situational factors for the survey we first performed a literature search which was followed by a qualitative interview study with patients, physicians and health care experts. As a result, 7 factors (e.g. "Reason for consultation" and "Number of therapeutic options") with 2 to 3 levels (e.g. "One therapeutic option" and "More than one therapeutic option") will be included in the study. For the survey the factor levels will be randomly combined to short stories describing different treatment situations. A randomized sample of all possible short stories will be given to at least 300 subjects (100 GPs, 100 patients and 100 members of self-help groups) who will be asked to rate how the decision should be made. Main outcome measure is the preference for participation in the decision making process in the given clinical situation. Data analysis will estimate the effects of the factors on the rating and also examine differences between groups. Discussion The results will reveal the effects of situational variations on participation preferences. Thus, our findings will contribute to the understanding of normative values in the medical decision making process and will improve future implementation of SDM and decision aids.